Study on the properties of perovskite materials under light and different temperatures and electric fields based on DFT. Issue 35 (2nd June 2020) - Diao, Xin-Feng; Tang, Yan-lin; Xiong, De-Yong; Wang, Ping-Rui; Gao, Li-ke; Tang, Tian-yu; Wei, Xiao-Nan; Zhang, Hai-Rong; Xu-Pu wu,; Ji, Shen-Tong
Abstract : The photoelectric conversion efficiency of perovskite solar cells has improved rapidly, but their stability is poor, which is an important factor that restricts their commercial production. Abstract : The photoelectric conversion efficiency of perovskite solar cells has improved rapidly, but their stability is poor, which is an important factor that restricts their commercial production. This paper studies the physical and chemical stability of perovskite solar cells based on first principles. It is well known that methylamido lead iodide compounds and methylamino lead iodide compounds are easily degraded into NH2 CHNH2 I, CH3 NH3 I and PbI2 . First, the chemical stability of the above two perovskite-type solar cell materials is discussed by calculating the binding energy. Then, their phonon scattering lines, state density and thermodynamic properties are calculated and analyzed, and the work functions of different types of crystals along different planes such as [1 0 0], [0 1 0 0], [0 0 1] and [1 1 1] are calculated. The results show that the work function of the methylamine iodized lead compound is greater than that of the methylamidine iodized lead compound, which means that the electrons of the methylamidine iodized lead compound escape more easily and the carrier transfer efficiency is higher under the same conditions. Finally, the effects of different temperatures, different electric fields and light on the two kinds of crystal materials are analyzed. This provides theoretical guidance for us to improve the stability of perovskite materials experimentally.